A financeirização da preservação ambiental no Brasil e as cotas de reserva ambiental - Carneiro, Laís Machado Papalardo de Moraes (2019)
The Environmental Reserve Quotas are an instrument brought by Law n. 12,651, dated May 25, 2012, which proposes to optimize agricultural production and reconcile it to environmental preservation through negotiable securities in the financial market. It is a legal and economic instrument inserted in the logic of environmental preservation through the commercialization of speculative titles, which, in this case, are extensions of preserved forest. Despite its formal existence in Law no. 4,771, dated September 15, 1965, the experience brought by the new law is still quite recent, its applicability, realization, effectiveness, implications and possible misrepresentations of its initial purposes being unclear. The analysis is based on what is most relevant on the subject, adopting as theoretical framework the idea of the author Amyra El Khalili that today we live a worldwide tendency to the financialization of nature, translated into a commoditization of natural assets, allied to the theory of Frais Ost, that nature undergoes a process of reification over the years. From this, it is demonstrated that the CRAs are instruments that represent a technical and / or political solution to the problem of deforestation generated by unsustainable agricultural production, combined with other public policies and efficient monitoring. Therefore, it is proposed to discuss what is the financialization of nature and what are the main criticisms of this global trend, specifically the CRA, in the context of a Forest Code sanctioned in an environment of tension between farmers and environmentalists. The work will seek to show that the CRA can be a useful tool to reduce the impacts of deforestation, but that, taken in isolation, does not face the bigger problem that nature is reduced to a simple commodity.